Empowering Natural Medicine: Combining Brotowali Extract (T.Crispa) with Lampung Natural Zeolite to Improve Diabetic Wound Healing - Mulyati, Lia; Wulandari, Afni; Devi, Fitria Kusuma; Rahayuningrat, Nurunnisa (Universitas Muhammadiyah Yogyakarta, 2024)
Background: Diabetic ulcers are a serious complication that often occurs in people with diabetes mellitus. The complication leads to amputation and causes disability in about 30% of patients.Objective: The study aims to test the effectiveness of an ointment formulation containing brotowali extract with a combination of Lampung natural zeolite (ZAL) in the healing process of diabetic ulcers.Methods: The research method used is quasi-experimental with a control group. The sample of this study used mice, with a total of 6 in each group. Before the intervention, blood sugar levels in the samples were increased by injecting streptozotocin. The study was conducted for 14 days. The Mann-Whitney test was used to analyze the data obtained.Results: The results showed a significant difference in the percentage of wound closure between the control group and the intervention group with p=0.002.Conclusion: Based on these findings, it can be concluded that an ointment formulation containing brotowali extract with a combination of ZAL effectively accelerates the wound healing process in diabetic mice. Brotowali extract ointment with a combination of Lampung natural zeolites can be used as an alternative in wound care for patients with diabetes mellitus based on herbs and local wisdom so that it will be more easily accepted in the community.